Institutionalizations of Mathematics Teaching and the Character of Mathematical Scientific Discourse. Observations from the Perspective of Pre-Modern History - Høyrup, Jens
Preprint; S. 3-11: Mesopotamia: Scribal computation and scribal school mathematics.